The impact of rising temperatures on tourism movement in Lattakia city (A survey study). - ناصر لميس; رياض قره فلاح (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Temperature is one of the most important elements affecting tourism attraction in the presence of natural and historical attractions, in addition to basic tourist services in the city of Lattakia. This research aims to study the impact of rising temperatures on tourism movement in the by analyzing the respornses of a random sample of Lattakia residents through questionnaire consisting of three questions distributed to 100 individuals based on variables (gender, age group, employment status, educational level, income level, and family size) to determine their tourist destination. The questionnaire was analyzed using standard statistical analytical methods at a significance level of 5% revealing no significant difference in opinions between genders, but significant differences among various age groups, there were significant differences between govemment employees and non-employees, as well as between private sector workers and self-employed individuals. Educational differences were significant between secondary and lower education levels. Similarly, there were significant differences between higher and lower income groups, while family size had no significant impact on the responses.